Low back pain and associated risk factors among health science undergraduates - Nor Azlin Mohd Nordin; Devinder Kaur Ajit Singh; Lim, Kanglun (Universiti Kebangsaan Malaysia, 2014)
Identification of associated risk factors is important to enable successful implementation of low back pain prevention strategies. To date, there is limited research data on back pain among young adults in Malaysia despite an increasing incidence of this disabling condition worldwide. A cross-sectional survey was conducted to determine the incidence of low back pain (LBP) and associated factors among health science undergraduates. A self-administered questionnaire was distributed to full time students of a main public university. One hundred and forty undergraduates; mean age 21.4±1.3 years, 70% female, 60% in year 3 of study, participated in the survey. The results showed that 31% spent between 6 and 8 h and another 31% spent more than 9 h sitting in a day. Twelve percent of the undergraduates rated their fitness level as ‘poor’. The incidence of LBP was 40.3% among the undergraduates. LBP incidence was associated with age (X2=12.1, p=0.007), years of study (X2=8.7, p=0.03), self-rated physical fitness (X2=7.0, p=0.02) and hours spent sitting (X2 =8.7, p=0.03). Gender, body mass index and hours spent in sports and physical activity were not associated with LBP. The findings from this study demonstrate that physical fitness and sitting duration is associated with low back pain among health science undergraduates. Health science undergraduates should improve their physical fitness, practice frequent breaks and stretching during sitting. This will help to minimize LBP related to decreased fitness levels and prolonged sitting.